El sistema vecinal y sus categorías en Navarra, a finales del Antiguo Régimen - Madariaga Orbea, Juan; Serralvo Gómez, Javier (Huarte de San Juan. Geografía e Historia, 1998)
This report approches, in first place, the caracterization of the neigbourshood system in the Basque-Navarre Country, including situation in Navarre in 1.726, based in the recount of "Fuegos" of that year. Once stablished a taxonomie of the different names and/or neighbour cathegories (neighbour, resident, owner, inhabitant,...), possible relations and divergencies between them are surched, stablishing finally their distribution all over territory's cartography.
Keywords: Municipality; neighbour; resident; Navarra